Asymmetric Organocatalytic Direct C(sp2)H/C(sp3)H Oxidative Cross‐Coupling by Chiral Iodine Reagents1. (19th February 2014) - Wu, Hua; He, Yu‐Ping; Xu, Lue; Zhang, Dong‐Yang; Gong, Liu‐Zhu
Abstract An asymmetric organocatalytic direct CH/CH oxidative coupling reaction of N1, N3‐diphenylmalonamides has been well established by using chiral organoiodine compounds as catalysts, wherein four CH bonds were stereoselectively functionalized to give structurally diverse spirooxindoles with high levels of enantioselectivity. More importantly, the findings indicated that chiral hypervalent organoiodine reagents can serve as alternative catalysts for the creation of enantioselective functionalization of inactive CH bonds.